Proyecto de la Ley Orgánica de Movilidad Humana, y los derechos humanos de las personas con discapacidad en migración - Espinosa Rivadeneira, Edgar Patricio (2017)
Ecuador's socio-economic conditions have led many people to emigrate from their country of origin, this because of the lack of job opportunities and their living conditions that want to be improved when they go to another country to provide what they are looking for. The migratory studies do not reflect the mobility of people with disabilities, nor are there statistics on this population and in public migration policy this sector is invisibilized. Within the first chapter are figures of persons with disabilities who have migrated, but this in an international and global context. In Ecuador, there are no reliable data on the migratory movement of people with disabilities, either on the way to or from Ecuador. The second chapter addresses public policies created for people with disabilities, their regulatory and enforcement bodies. This chapter refers to the different types of disabilities recognized in Ecuador. In the third chapter a short analysis is made on the Organic Law of Human Mobility in its articulation on people with disabilities, what is proposed in this legislation and the lack of specificity to this group. Political actors as proponents of the bill, and, testimony of a disabled migrant who left Ecuador and returned. Finally, in the fourth chapter, we reach the conclusions of this research on people with disabilities in human mobility and their universal human rights. Here we answer the research questions that were raised in the dissertation project and make recommendations.